The Influence of Digital Marketing, Menu Diversity, and Service Quality on Customer Loyalty - Ufi Rumefi; Agus Andi Subroto; Jihad Agil Maulana Kusuma (Publikasi Indonesia, 2025)
The background of this research is based on the increasingly competitive culinary business landscape in the digital era, where digital marketing strategies, menu variations, and customer service play a crucial role in maintaining customer loyalty. This research aims to test and analyze the influence of digital marketing, menu diversity, and service quality on customer loyalty among